Czy za skandale dopingowe w UE będą płacić sponsorzy? Doping ryzykiem reputacyjnym i presją dla organizacji finansujących sport i instytucji regulacyjnych - Pepłowska, Aleksandra (Kultura-Społeczeństwo-Edukacja, 2025)
Operating at the intersection of competition, business and political issues, contemporary sport faces challenges from the growing expectations of sponsors and an increasingly demanding public – either spectators or voters. This article aims to demonstrate that, with the development of EU sustainability reporting regulations, sports sponsors will be required to integrate reputational risks associated with doping into their management strategies. The first section explores the impact of EU regulations, in particular the Corporate Sustainability Reporting Directive (CSRD) and the European Sustainability Reporting Standards (ESRS), on the obligations of sports sponsors and their perception of the reputational risks associated with doping. Through the example of incidents such as the suspension of Iga Świątek in 2024, it demonstrates the increasing pressure on sponsors and sports organisations to implement more effective anti-doping mechanisms. Following this, a study of reputational risk in sport is conducted, highlighting its importance in ESG management strategies and its impact on corporate investment and communication decisions. Subsequently, a discussion of the ineffectiveness of existing anti-doping policies and inequalities in enforcement around the world follows, highlighting the need for international institutions to harmonise their actions. The article is theoretical and review-based. The analysis of documents is conducted chronologically and by issue, which organises scattered threads and allows regulatory gaps to be identified. The research gap in the literature regarding sponsors’ perspectives on doping scandals provides a basis for new reflections on the role of business in contemporary sport and its social responsibility.